PEMBERDAYAAN ANAK JALANAN DALAM PANDANGAN ISLAM - Miftahur Ridho (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
The aim of this paper is to show that Islam is a children and youth friendly religion. This friendliness is reflected by the fact that Islamic perspective towards children and youth related social problem is loaded with ideas of advocating their rights and excoriating the perpetrators of abuse toward them. Thus, this paper deals with stories of the prophet Muhammad concerning social welfare of children and youth. Those stories will be analyzed according to the implementation of social services based on the promotion of human rights model. Ideal concept of children within the stories analyzed in this paper indicates that Islam positions children and youth in a unique place among groups of society. Therefore, provision of social services intended to increase the wellbeing of children and youth must consider their spiritual development as well as cultural aspects of their social setting.